PENERAPAN PEMBELAJARAN KOOPPERATIF TIPE JIGSAW DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Syarifah, Syarifah (FORUM PAEDAGOGIK, 2014)
AbstractThis research focusesd on the low achievement of mathematical learning in problem solving, mathematical communication and students activity in mathematical learning was low, response to mathematical learning activity was low and mathematical learning which was applied less efficient. Therefore, it needs an effort to improve learning process, problem solving and mathematical communication. One of effort was the implementation of jigsaw cooperative learning. This research is class action research which applied on SMP Negeri 5 Padang Sidimpuan. The subject of this research was grade VII that consist of 40 students. This research was developed by teacher’s book, students’ book, LAS and instrument which consist of problem solving test and mathematical communication test. The study comprised two cycles and the test given at the end of each cycle. It concluded that the implemantation of jigsaw cooperative learning are able to improve the students’ ability in mathematical communication, active students activity, teachers’ ability in managing learning process and students’ positive response on learning devices.Keywords : Jigsaw Cooperative Learning, Problem Solving, Mathematical Communication.